Status resistensi terhadap fosfin pada Tribolium castaneum Herbst (Coleoptera: Tenebrionidae) dari gudang penyimpanan biji kakao di Makassar Sulawesi Selatan - Sri Widayanti; Dadang Dadang; Idham Sakti Harahap (Jurnal Entomologi Indonesia, 2017)
Control of postharvest pest on cocoa beans during storage is generally conducted by fumigation with phosphine. Long-term exposure to phosphine and improper fumigation practices could stimulate the development of resistant strains against phosphine. The aims of this research were to know the resistance status of red flour beetle Tribolium castaneum Herbst (Coleoptera: Tenebrionidae) against phosphine from cocoa bean storages in Makassar, South Sulawesi and to conduct the field efficacy test of phosphine against insects resistant strain to confirm their resistance status. The study was conducted by collecting T. castaneum from five different cocoa beans storages in Makassar. Resistance status was tested in the laboratory using the standard method recommended by FAO and by conducting field efficacy test on adult strains resistant to phosphine. The results showed the presence of insect resistance to phosphine. Adult, pupae, and larvae of T. castaneum were found to be resistant to phosphine with the resistance factors of 1.15–8.08, 1.58–13.63, 1.53–3.25, respectively. The results of field efficacy tests showed that dosage 2 tablets/m3 was effective in controlling resistant strain of adult, pupae, and larvae of T. castaneum.